Mathematical Reasoning in Mathematics Learning on Pyramid Volume Concepts - Ulvatun Niswah; Abd Qohar (Universitas Malikussaleh, Aceh Utara, Indonesia, 2020)
The purpose of this study was to describe the standard process of mathematical reasoning in learning on pyramid volume concepts. The study was a study with descriptive qualitative approach, carried out by peer teaching in the classroom. The subjects of this research were Class B Postgraduate 2018 (S2) students, State University of Malang. The standard process of this activity was to recognize reasoning and verification as a basic aspect in mathematics, to make and investigate mathematical conjecture, to find out how to develop and evaluate mathematical arguments and verification, to find out how to choose and use various types of reasoning and proof methods.